American parishes: remaking local Catholicism - Adler, Gary J. Jr.; Bruce, Tricia Colleen; Starks, Brian (Catholic practice in North America, 2019)
Introduction:What is a parish? Why look at Catholic parishes /Gary J. Adler Jr., Tricia C. Bruce, Brian Starks --A brief history of the sociology parishes in the United States /Tricia C. Bruce --Studying parishes: lessons and new directions from the study of congregations /Nancy T. Ammerman --The shifting landscape of US Catholic parishes, 1998-2012 /Gary J. Adler Jr. --Stable transformation: Catholic parishioners in the United States /Mark M. Gray --Power in the parish /Brett C. Hoover --Liturgy as identity work in predominantly African American parishes /Tia Noelle Pratt --A house divided /Mary Jo Bane --Parishes as home and hubs /Kathleen Garces-Foley --Preparing to say "I do" /Courtney Ann Irby --A sociologist looks at his own parish: a conversation with John A. Coleman, SJ /John A. Coleman, SJ, with editors Gary J. Adler Jr., Tricia C. Bruce, and Brian Starks --Conclusion:Parishes as the embedded middle of American Catholicism /Gary J. Adler Jr., Tricia C. Bruce, Brian Starks.